Before Military Intervention
XVII, 213 p. 6 illus., 5 illus. in color.
Keywords: This book explores the natures of recent stabilisation efforts and global upstream threats. As prevention is always cheaper than the crisis of state collapse or civil war, the future character of conflict will increasingly involve upstream stabilisation operations. However, the unpredictability and variability of state instability requires governments and militaries to adopt a diversity of approach, conceptualisation and vocabulary. Offering perspectives from theory and practice, the chapters in this collection provide crucial insight into military roles and capabilities, opportunities, risks and limitations, doctrine, strategy and tactics, and measures of effect relevant to operations in upstream environments. This volume will appeal to researchers and practitioners seeking to understand historical and current conflict. Timothy Clack is Fellow and Lecturer of St Peter’s College and Senior Research Fellow of the Changing Character of War Centre, University of Oxford, UK. Robert Johnson is Director of the Changing Character of War Centre and Senior Research Fellow of Pembroke College, University of Oxford, UK.